The associations between bariatric surgery and hip or knee arthroplasty, and hip or knee osteoarthritis: Propensity score-matched cohort studies - Theresa Burkard; Dag Holmberg; Per Wretenberg; Anders Thorell; Thomas Hügle; Andrea M. Burden (Osteoarthritis and Cartilage Open, 2022)
Objective: To investigate the associations between bariatric surgery and hip or knee arthroplasty, and secondary care hip or knee osteoarthritis (OA). Methods: We performed cohort studies using data from Swedish nationwide healthcare registries. Patients aged 18–79 years who underwent bariatric surgery between 2006 and 2019 were matched on their propensity score (PS) to up to 2 obese patients (“unexposed episodes”) in risk-set sampling. After a 1-year run-in period, episodes were followed in an “as-treated” approach. Using Cox proportional hazard regression, we calculated hazard ratios (HR) with 95% confidence intervals (CIs) of hip or knee arthroplasty overall and in subgroups of age, sex, joint location, arthroplasty type, bariatric surgery type, and by duration of follow-up if proportional hazard assumptions were violated. In a secondary cohort, we assessed the outcome incident secondary care hip or knee osteoarthritis (OA). Results: Among 39‘392 bariatric surgery episodes when compared to 61’085 ​PS-matched unexposed episodes (47′594 unique patients), the risk of hip or knee arthroplasty was strongest increased within the first three years of follow-up (HR 1.79, 95% CI 1.56–2.07), decreased thereafter, but remained elevated throughout follow-up. In a secondary cohort of 37′929 exposed when compared to 58′600 ​PS-matched unexposed episodes, the risk of hip or knee osteoarthritis was decreased (HR 0.84, 95% CI 0.79–0.90). Conclusion: Bariatric surgery is associated with increased risks of hip or knee arthroplasty, but also with decreased risks of secondary care OA. This contradiction supports the hypothesis that bariatric surgery may act as an enabler for hip or knee arthroplasty.